2021
DOI: 10.1177/23259671211035741
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Use of Flexible and Rigid Reaming Systems Through an Anteromedial Portal for Femoral Tunnel Creation During Anterior Cruciate Ligament Reconstruction: A Systematic Review

Abstract: Background: Recent studies have suggested that femoral tunnel drilling during anterior cruciate ligament (ACL) reconstruction (ACLR) with the use of a flexible reaming system through a standard anteromedial portal (AM-FR) may result in a different tunnel geometry compared with a rigid reamer through an accessory anteromedial portal with hyperflexion (AM-RR). Purpose: To summarize radiologic, anatomic, and clinical outcomes from available studies that directly compared the use of AM-FR versus AM-RR for independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(151 reference statements)
0
3
1
Order By: Relevance
“…The use of the FR for femoral tunnel creation results in a more anteverted femoral tunnel position compared with the use of a RR, whereas the intra-articular femoral tunnel aperture location is not different. 27 Although this difference in resultant tunnel geometry has been described, there was no significant difference in tunnel violation seen in this study depending on technique used. Outside-in ACL femoral tunnel creation also has been suggested by several authors to potentially allow more precise femoral tunnel positioning and reduce convergence with LET graft fixation, but has not presently been compared with other modern anatomic techniques.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The use of the FR for femoral tunnel creation results in a more anteverted femoral tunnel position compared with the use of a RR, whereas the intra-articular femoral tunnel aperture location is not different. 27 Although this difference in resultant tunnel geometry has been described, there was no significant difference in tunnel violation seen in this study depending on technique used. Outside-in ACL femoral tunnel creation also has been suggested by several authors to potentially allow more precise femoral tunnel positioning and reduce convergence with LET graft fixation, but has not presently been compared with other modern anatomic techniques.…”
Section: Discussioncontrasting
confidence: 41%
“… 19 , 20 Degree of knee flexion during ACL femoral tunnel creation also yields a differing tunnel orientation within the femur. 27 , 28 Kittl et al. 18 found that ACL femoral tunnel creation in lesser degrees of knee flexion (110-120° vs 130-140°) reduced the incidence of femoral tunnel conflict in combined ACL-R using an AMP technique and LET.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that while previous literature 18 exists to suggest that ACLR using AM-FR for femoral tunnel trends toward resulting in a more anatomic ACLR, this study lacks direct radiologic evidence that this difference manifested within our study population. Finally, as a literature review 18 shows that the radiologic and anatomic differences resulting from AM-FR and AAM-RR are more evident when deep flexion is unable to be achieved, it is possible that there would have been a difference observed in patients with less intrinsic flexibility, such as patients who are more muscular or have larger body habitus. This study is more representative of the overall population undergoing ACLR, however, and is therefore more translatable than isolated subgroup analysis based on revision procedures or a certain population characteristic.…”
Section: Discussionmentioning
confidence: 88%
“…Previous cadaver studies reported that a significantly longer femoral tunnel could be achieved with a flexible guide pin than with a rigid guide pin [ 11 , 12 ]. A recently published systemic review reported that a clinical application of a flexible guide pin resulted in a longer and more anteverted femoral tunnel than a rigid guide pin [ 13 ]. In an attempt to overcome the inherent limitations of the transportal technique, the retrograde drilling method was introduced [ 14 ].…”
Section: Introductionmentioning
confidence: 99%